Bioherbicidal properties of Parthenium hysterophorus, Cleome rutidosperma and Borreria alata extracts on selected crop and weed species - Motmainna, Mst; Juraimi, Abdul Shukor; Uddin, Md. Kamal; Asib, Norhayu; Mominul Islam, A. K. M.; Hasan, Mahmudul (Multidisciplinary Digital Publishing Institute, 2021)
Natural product-based herbicides could be the effective alternatives to synthetic chemical herbicides for eco-friendly weed management. This research, therefore, was conducted to identify the phytotoxic properties of Parthenium hysterophorus L., Cleome rutidosperma DC. and Borreria alata (Aubl.) DC. with a view to introducing them as a tool for natural herbicide development. The methanol extracts of these plants were examined on the germination and growth of Zea mays L., Oryza sativa L., Abelmoschus esculentus (L.) Moench and Amaranthus gangeticus L., Oryza sativa f. Spontanea Roshev. (Weedy rice), Echinochloa colona (L.) Link., Euphorbia hirta L., and Ageratum conyzoides L. under laboratory and glasshouse conditions. A complete randomized design (CRD) with five replications and randomized complete block design (RCBD) with four replications were laid out for laboratory and glasshouse experiments, respectively. In the laboratory experiment, three plant extracts of 0, 6.25, 12.5, 50, and 100 g L−1 were tested on survival rate, hypocotyl, and radicle length of eight test plant species. No seed germination of A. conzyoides, E. hirta, and A. gangeticus were recorded when P. hysterophorus extract was applied at 50 g L−1. C. rutidosperma had the same effect on those plants at 100 g L−1. In the glasshouse, similar extracts and concentrations used in the laboratory experiments were sprayed on at the 2–3 leaf stage for grasses and 4–6 for the broadleaf species. Tested plants were less sensitive to C. rutidosperma and B. alata compared to P. hysterophorus extract. Among the weeds and crops, A. conyzoides, E. hirta, A. esculentus and A. gangeticus were mostly inhibited by P. hysterophorus extract at 100 g L−1. Based on these results, P. hysterophorus was the most phytotoxic among the tested plant extracts and could be used for developing a new natural herbicide for green agriculture.